2013
DOI: 10.5596/c13-061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Course Integrated Library Instruction in an Undergraduate Nursing Program

Abstract: Introduction: Many faculty in two Schools of Nursing found that students in the fourth year of the Bachelor of Nursing program were not well equipped to perform information literacy activities efficiently and effectively, such as doing research to support their daily work. A course-integrated information literacy program was implemented at both sites, which left some students having very little information literacy training, whereas others who started the program in later years had information literacy trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…While numerous studies have examined information literacy skills in the context of nursing education at the undergraduate and graduate levels (Farrell et al., ; Flood et al., ; Jacobs et al., ; McCulley & Jones, ; Miller & Neyer, ; Schutt & Hightower, ; Verhey, ; Wahoush & Banfield, ), there is a lack of research addressing training programmes at the two‐year level. A few studies (Argüelles, ; Beck et al., ; Courey et al., ) have examined the integration of information literacy instruction into the curriculum of associate‐level programmes at community colleges in the United States using the ALA's Standards (2000) or Framework (2015).…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have examined information literacy skills in the context of nursing education at the undergraduate and graduate levels (Farrell et al., ; Flood et al., ; Jacobs et al., ; McCulley & Jones, ; Miller & Neyer, ; Schutt & Hightower, ; Verhey, ; Wahoush & Banfield, ), there is a lack of research addressing training programmes at the two‐year level. A few studies (Argüelles, ; Beck et al., ; Courey et al., ) have examined the integration of information literacy instruction into the curriculum of associate‐level programmes at community colleges in the United States using the ALA's Standards (2000) or Framework (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous studies have shown inconsistencies and conflicting results about the validity of training in the form of one-off sessions, as long lasting impact cannot be guaranteed after only one training (Carlock & Anderson, 2007;Farrell, Goosney & Hutchens, 2013;Ilic, Tepper & Misso, 2012). This study has demonstrated that the NICE SCS delivery format, over the course of five years, has indeed had an impact on improving information search skills in students, particularly by increasing self-confidence in information seeking and contributing to a wider use of specialised (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Information literacy is being taught to nursing students with varying levels of success. While information literacy is important, it is also difficult to teach and assess effectively, and at times outcomes are only moderately improved (Farrell, Goosney, & Hutchens, 2013;Moreton & Conklin, 2015). According to a survey of instruction librarians, information literacy programs in higher education are often limited to first year instruction, although disciplinespecific instruction for undergraduates is also available (Julien, Gross, & Latham, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers chose the survey as a data collection tool to reach a large number of geographically dispersed respondents with a set of standardized questions. Survey question topics and themes were informed by questionnaire-based research studies on nurses' and nursing students' information behaviour (Argyri, Kostagiolas, Diomidous, 2014;Baro & Ebhomeya, 2013;Intas et al, 2016;Kumaran & Chipanshi, 2015;Majid et al, 2011;O'Leary & Ni Mhaolrúnaigh, 2012;Sarbaz,et al, 2016;Wahoush & Banfield, 2014), specifically those studies which included their survey instruments (Dee & Stanley, 2005;Farrell, Goosney, & Hutchens, 2013;Pravikoff, Tanner, & Pierce, 2005). The survey questions, in a variety of formats including multiple choice and open-ended questions, were pre-tested and revised where necessary to prevent misinterpretation and bias.…”
Section: Data Collection and Analysismentioning
confidence: 99%